1992
DOI: 10.1093/milmed/157.3.111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Povidone-Iodine Irrigation on the Preoperative Chemical Preparation of the Eye

Abstract: Preoperative eyes which had been treated with gentamicin for one-half day were subjected to one of two povidone-iodine (PI) preparations. The control eye was prepared using a previously described 5% PI one-drop technique, while the paired eye was irrigated with a 0.02% PI solution. Aerobic and anaerobic bacterial cultures were taken of each eye before and after PI applications. Statistical analysis of the data indicates that both techniques were equally effective in reducing surface colonization of the anaerob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
1
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
1
8
1
2
Order By: Relevance
“…The type of bacteria isolated were consistent with the bacterial flora found in previous studies. [9][10][11][12] None of these either before or after irrigation showed a significant difference between the treatment groups. Twenty six of the 100 cultures were "sterile" (yielded no cultured organism) before irrigation, and 22 of these were also "sterile" following irrigation.…”
Section: Quantitative Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The type of bacteria isolated were consistent with the bacterial flora found in previous studies. [9][10][11][12] None of these either before or after irrigation showed a significant difference between the treatment groups. Twenty six of the 100 cultures were "sterile" (yielded no cultured organism) before irrigation, and 22 of these were also "sterile" following irrigation.…”
Section: Quantitative Datamentioning
confidence: 99%
“…Povidone-iodine stock solution is 10%, comprising 90% water, 8.5% povidone-iodine, 1% available iodine, and iodide. 3 Previous studies have shown that 5% povidone-iodine effectively decreases the bacterial flora of the ocular surface and adnexae, [9][10][11][12] and thus theoretically decreases the risk of endophthalmitis, while other large studies have demonstrated 5% povidone-iodine to directly decrease the incidence of endophthalmitis. 1 13 More dilute concentrations have been studied in vivo in dogs' eyes where 0.2% povidone-iodine was shown to be equally as bactericidal as 1% and 5% povidone-iodine.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bis anhin wurde bei den präoperativen Desinfektionsstudien häufig die Keimzahl mittels Bindehautabstrichen verglichen [2,7,8,12,14,16,18,22]. Die Methode mittels mikrobiologischer Analyse der Schnittmesser ist erst in neuerer Zeit aufgetaucht.…”
Section: Diskussionunclassified
“…Für die Haut ist Povidon-Iod in einer 8 -10 % Lösung kommerziell erhältlich. Weit verbreitet in der Ophthalmochirurgie ist die kommerziell erhältliche 5 % topische Tropflösung (5 % Betadine Sterile Ophthalmic Prep Solution; Alcon Laboratories, Inc, Fort Worth, Texas, USA) [10,28], obwohl Verdün-nungen bis 0,02 % ähnlich stark desinfizierende Wirkungen zeigen [14,16]. Während bei früheren Studien die Keimzahl meistens mittels konjunktivaler Abstriche verglichen wurde, analysierten neuere Studien die Kontaminationsrate intraoperativ benutzter Schnittmesser.…”
Section: Introductionunclassified